Randomized controlled multicenter trial on the effectiveness of the collagen hemostat Sangustop® compared with a carrier-bound fibrin sealant during liver resection (ESSCALIVER study, NCT00918619) - Moench, Christian; Mihaljevic, A. L.; Hermanutz, V.; Thasler, W. E.; Suna, K.; Diener, Markus K.; Seehofer, D.; Mischinger, H. J.; Jansen-Winkeln, B.; Knaebel, H. P.; Bechstein, Wolf Otto (Langenbeck's archives of surgery, 2014)
Despite improvements in liver surgery over the past decades, hemostasis during hepatic resections remains challenging. This multicenter randomized study compares the hemostatic effect of a collagen hemostat vs. a carrier-bound fibrin sealant after hepatic resection.